THE EFFECT OF VOLTAGES IN THE ELECTROCOAGULATION PROCESS ON DECREASING FE AND MN LEVELS - Ria Muliyana; Masthura Masthura; Abdul Halim Daulay (Universitas Islam Negeri Sumatera Utara Medan, 2019)
Research on the effect of electric voltage on the electrocoagulation process in reducing levels of heavy metals in water. This study aims to determine the metal content Fe (Iron) and Mn (Manganese) dug well water by varying the electrical voltage of 3, 6, 9, and 12 volts. this research use dug well water which come from Teluk Piyai Pesisir Village Kubu sub-district Rokan Hilir district Riau Province. Test results on the electrocoagulation method with electrical voltage 3 volt metal content Fe 0,002 mg/l and metal content Mn <0,0034 mg/l, electrical voltage 6 volt metal content Fe 0,003 mg/l and metal content Mn0,003 mg/l, electrical voltage 9 volt metal content Fe 0,004 mg/l and metal content Mn 0,007 mg/l, and electrical voltage 12 volt metal content Fe 0,001 mg/l and metal content Mn 0,005 mg/l. From variations in electrical voltage using aluminum electrodes that meet the Minister of Health Regulations standards RI No. 416/MENKES/PER/IX/1990 that on voltage 3, 6, and 12 volt. Keywords: Electrical Voltage, Electrocoagulation, and Heavy Metal.